2009
DOI: 10.1128/jvi.00576-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type 16 Infection of Human Keratinocytes Requires Clathrin and Caveolin-1 and Is Brefeldin A Sensitive

Abstract: Human papillomavirus type 16 (HPV16) has been identified as being the most common etiological agent leading to cervical cancer. Despite having a clear understanding of the role of HPV16 in oncogenesis, details of how HPV16 traffics during infection are poorly understood. HPV16 has been determined to enter via clathrin-mediated endocytosis, but the subsequent steps of HPV16 infection remain unclear. There is emerging evidence that several viruses take advantage of cross talk between routes of endocytosis. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 73 publications
4
79
0
6
Order By: Relevance
“…HPV is then thought to escape into the cytoplasm and travel by an unknown, microtubule-dependent route to the nucleus where virus replication occurs (12,19). One study concluded that HPV16 traffics through the endoplasmic reticulum (ER) (11). The L2 protein appears to be important for proper intracellular trafficking, as does binding of sorting nexin 17 to an internal segment of L2 (21)(22)(23).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…HPV is then thought to escape into the cytoplasm and travel by an unknown, microtubule-dependent route to the nucleus where virus replication occurs (12,19). One study concluded that HPV16 traffics through the endoplasmic reticulum (ER) (11). The L2 protein appears to be important for proper intracellular trafficking, as does binding of sorting nexin 17 to an internal segment of L2 (21)(22)(23).…”
mentioning
confidence: 99%
“…Cyclophilin B and the proteases furin and γ-secretase play essential but not clearly understood roles during HPV entry (16)(17)(18)(19). After HPV is internalized, capsid disassembly is initiated in the endosome by acidification (11,15,20). HPV is then thought to escape into the cytoplasm and travel by an unknown, microtubule-dependent route to the nucleus where virus replication occurs (12,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultures of HaCaT cells, a spontaneously immortalized human keratinocyte cell line, were maintained in DMEM (Sigma-Aldrich), supplemented with 10% (v/v) sterile-filtered fetal bovine serum (Sigma-Aldrich), 2% L-glutamine (Invitrogen), 100 g/ml streptomycin, and 100 IU/ml penicillin (Invitrogen) at 37°C in a humidified atmosphere with 5% CO 2 . For inhibition of the endoplasmic reticulum/Golgi secretory transport, 25 ng/ml brefeldin A (Sigma-Aldrich) was added to a HaCaT cell culture for 48 h (25). Palmitoylation was metabolically inhibited by treating HaCaT cultures with 2-bromo-palmitate (SigmaAldrich) overnight at 50 M (26).…”
Section: Methodsmentioning
confidence: 99%
“…In order to further clarify the membrane localization of PLSCR1, we next investigated whether palmitoylation is necessary for the secretion of PLSCR1. Therefore, HaCaT cells were cultured under the condition where palmitoylation was metabolically prevented by 2-bromo-palmitate, a competitive inhibitor of the transfer of palmitoyl-CoA to the cysteinoyl thiol (25). However, no altered secretion of PLSCR1 was observed when comparing the supernatant and cell lysate of HaCaT cells stably overexpressing eGFP-PLSCR1 in the presence or absence of 2-bromo-palmitate (2-BP) (Fig.…”
Section: Intra-cellular Column)mentioning
confidence: 99%